THE ROLE OF TEACHERS IN AWARENESS OF OCCUPATIONAL SAFETY AND HEALTH (OSH) VOCATIONAL SCHOOL STUDENTS - Wahrini, Retyana; Nuridayanti, Nuridayanti; Makmur, Elfira (Three E Science Institute, 2019)
This study aims to determine the effect of the role of the teacher and the occupational safety and health (OSH) climate on occupational safety and health increasing awareness in the electrical installation workshop of the Vocational High School. This research is an Ex-post Facto research. The population of the research is the XII grade students of Vocational High School 1 Sedayu Special Region of Yogyakarta with a total of 366 students and a sample of 188 students. The number of trials respondents 30 students. The sampling technique uses random sampling and data is taken using a questionnaire instrument. The validity of the questionnaire instruments done by item using analysis Product Moment correlation formula and reliability testing using the Cronbach Alpha. The results showed that (1) there is a positive and significant influence between the role of the teacher in occupational safety and health increasing awareness in the electrical installation workshop of vocational high school value 43.30 percent; (2) there is a positive and significant effect between the occupational safety and health climate on increasing occupational safety and health awareness in the electrical installation workshop of vocational high school value 43.40 percent; (3) there is a positive and significant influence between the role of teacher and occupational safety and health climate on occupational safety and health increasing awareness in the electrical installation workshop of vocational high school value 50.60 percent. The application of OSH will have an impact on increasing the productivity of the workforce and the company.